ANALISIS PENGARUH FAKTOR IKLIM DAN KEBAKARAN HUTAN/LAHAN TERHADAP KONSENTRASI PM10 DI KOTA PEKANBARU SELAMA KURUN WAKTU TAHUN 2011-2015 - Adi Candra; Thamrin Thamrin; Mubarak Mubarak (Jurnal Ilmu Lingkungan, 2017)
Land/Forest Fire and Climate Factor Influence Analysis of PM10 Concentrations in Pekanbaru City during the 2011-2015 Timeframe have been done. The purpose of this study to find out how big the influence of climate and forest/land to PM10 concentration and its impact on aviation and incidence of Acute Respiration Infection (ARI) disease in Pekanbaru City during the period 2011-201. The method used in this research is secondary data survey method located in Pekanbaru City Air Laboratory, BMKG Pekanbaru, Pekanbaru City Health Office, PT. Angkasa Pura II Pekanbaru and LAPAN. Data were analyzed statistically and discussed descriptively. The population in this study is all of the data for PM10 and climatic factors Sukajadi station records and other data from relevant agencies. Sampling was done by using purposive sampling method that is a diary within 24 hours of the PM10 and climatic factors are summed and then taken the average monthly. so that the sample observations from the years 2011-2015 as many as 60 samples (12 samples in one year). The results showed that climatic factors and forest / land fires (hotspots) affect the concentration of PM10 in Pekanbaru City. From 7 (seven) variables analyzed finally obtained 3 (three) variable very significant influence. The concentration of PM10 also affects the aviation activity and the incidence of ARI in Pekanbaru. Based on the research results can be concluded that the factors that greatly affect the concentration of PM10 is the event of forest fire and land (hotspot) next rainfall and the last is the wind speed. The incidence of ARI and the aviation activity in Pekanbaru City is also influenced by PM10 concentration